2018
DOI: 10.1002/jso.25151
|View full text |Cite
|
Sign up to set email alerts
|

Prospective implementation of a standardized screening protocol for deep venous thrombosis in abdominal surgical oncology patients

Abstract: Despite prophylaxis, the prevalence of occult DVT in abdominal oncologic surgery patients is considerable. Postoperative screening duplex can identify these events to guide management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…70 VTE was the outcome in 81 studies, 114,[117][118][119][120][121][122][123] ATE in 4 studies, 34,62,69,109 and a combination of ATE and VTE in 15 studies. 37,38,44,49,65,71,89,[93][94][95]102,103,111,115,116 The patents received thromboprophylaxis in 10 studies, 30,33,41,50,67,78,87,106,119,121 some patients received thromboprophylaxis in 19 studies, 3,44,59,61,66,73,81,85,86,90-92,99,101,104,108 111,113,115 and no thromboprophylaxis was used in 25 studies. 14,35,36,[38][39][40]42,43,46,…”
Section: Resultsmentioning
confidence: 99%
“…70 VTE was the outcome in 81 studies, 114,[117][118][119][120][121][122][123] ATE in 4 studies, 34,62,69,109 and a combination of ATE and VTE in 15 studies. 37,38,44,49,65,71,89,[93][94][95]102,103,111,115,116 The patents received thromboprophylaxis in 10 studies, 30,33,41,50,67,78,87,106,119,121 some patients received thromboprophylaxis in 19 studies, 3,44,59,61,66,73,81,85,86,90-92,99,101,104,108 111,113,115 and no thromboprophylaxis was used in 25 studies. 14,35,36,[38][39][40]42,43,46,…”
Section: Resultsmentioning
confidence: 99%
“…Abdominal procedures may overlap with oncologic surgery, a group of patients among which the incidence of VTE is high, with one study detecting occult postoperative DVT by surveillance duplex in 9.8% of patients despite the use of perioperative thromboprophylaxis. 17 For vascular surgery patients, who have a high incidence of postoperative VTE, the use of both mechanical and pharmacologic prophylaxis in the preoperative period led to a 75% reduction in postoperative VTE in one single center study. 18 Further study is necessary to investigate whether initiation of intensive preoperative prophylaxis, and extended post-operative pharmacologic therapy would be beneficial following these highest risk procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It was extensively reported that conventional open cholecystectomy is followed by activation of coagulation mechanism. 13,14 Bergqvist et al reported 7-10% incidence of VTE diagnosed by using the venography in patients having undergone conventional open cholecystectomy. 15 As opposed to conventional open cholecystectomy, LC is a minimally invasive procedure for gallbladder disease.…”
Section: Discussionmentioning
confidence: 99%